HUBUNGAN ANTARA ASUPAN ENERGI DAN AKTIFITAS FISIK DENGAN KEBUGARAN JASMANI - Ridwan, Muhammad; Lisnawati, Naintina; Enginelina, Emillia (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2017)
Background: Physical fitness or cardiorespiratory fitness is associated with a person's ability to perform activities or activities effectively and without excessive fatigue. Results of the survey by a team of developers Sport Development Index (SDI) in 2005 shows the level of physical fitness elementary school across Indonesia are comparatively low. Objective: To determine the relationship between energy intake and physical activity with the physical fitness of students from SD-IT Albina Purwakarta in school year 2016 Methods: This study used cross-sectional design with stratified random sampling and systematic random sampling methods in the sampling process.A numberof 33 students from class V SD-IT Albina Purwakarta participated in this study. Data of physical activity was measured using 24-hour recall physical activity, energy intake using 24-hour recall, and physical fitness using the Harvard Step Test.Data analysis using Pearson Product Moment and Rank-Spearman test. Result: Energy intake of the majority of respondents (54.5%) fall into the category deficits, physical activity all respondents (100%) is relatively light and the physical fitness of the respondents (81.8%) included in the low category. There was no significant association between energy intake and physical activity with physical fitness (p=0,413; p=0,297). Conclusion: There was no significant association between energy intake and physical activity with physical fitness.